Multiprocessor Scheduling meets the Industrial Wireless: A brief review - Gaitán Gutiérrez, Miguel (2019)
This survey covers schedulability analysis approaches that have been recently proposed for multi-hop and multi-channel wireless sensor and actuator networks in the industrial control process domain. It reviews results with a focus on WirelessHART-like networks. The paper address the mapping of multi-channel transmission scheduling to multiprocessor scheduling theory, and recognize it as the key aspect of the research direction covered by this survey. It also provides a taxonomy of the existing approaches concerning this direction, and discuss its main features and evolution. The survey identifies open issues, key research challenges, and future directions.